Evaluation of university teaching hospital websites in Nigeria - Mahmud, Murni; O.Raji, Shakirat; Abubakr, Adamu (Elsevier Ltd., 2013)
Hospital Websites could be used as a medium to enhance hospital services to the public through better design and intense delivery of content. These Websites are good sources of reference for general information about the hospital and thus can be used to empower users to learn about health, diseases and medication. The clinicians and specialists at the hospital could share and leverage their knowledge as well as provide the content about illness and their prevention. Generally, university teaching hospitals, which are government hospitals attached to universities, are centers for future clinicians and academics to learn and practice their knowledge and skills. It is a great source of medical knowledge that can be shared with the members of public, which can be realized through Hospital Websites. Websites could facilitate in creating and improving their presence and interactive communication practices between clinicians with patients and public. This paper presents the result of evaluation of selected University Teaching Hospital Websites (UTHW) selected from three main regions of Nigeria. The Usability and User Experience of the Hospital Websites were evaluated with the aim to provide better understanding of the design features and contents of the Hospital Websites that can offer positive experience and empower the users. Users who participated in the evaluation were given 6 tasks to locate and find specified information in the websites based on 10 Usability heuristics contained in the questionnaire in order to gather the users’ opinion about the websites. The accessibility and availability were also evaluated and the findings indicated each website has their own strengths and weakness that can be capitalized on for proposing guidelines for better design of Hospital Websites.